Mitigation of recurrent perturbation mortality is an important goal for river restoration and conservation of freshwater fish species - Hatch, Michael D.; Abadi, Fitsum; Porter, Michael D.; Cowley, David E. (Restoration ecology, 2022)
Human perturbations affect many aquatic ecosystems globally. We use age‐structured matrix population models to explore how population growth rates in short‐lived freshwater fish are affected by recurrent environmental perturbations to river ecosystems. Simulations are summarized to reveal how species‐specific fitness characteristics contribute to population sustainability in habitats subject to recurrent perturbation. Deterministic calculations are used to estimate time to population recovery with successive years of intermittence disturbance, followed by post‐perturbation equilibrium conditions. Perturbation that reduces only juvenile survival has a shorter recovery time to initial population size and greater resilience of population growth than when adult survival is reduced. Consecutive occurrences of perturbation lengthen recovery time nonlinearly, more notably when adults experience perturbation mortality. We illustrate with an example how managers could identify multiple options to mitigate recurrent ecosystem perturbations by reducing perturbation frequency and/or mitigating perturbation mortality. Our simulations suggest parameter approximations for a hypothetical species provide a useful frame of reference for river restoration and conservation when life history data are lacking for a specific species of concern.